Lithium metal composite oxide, positive electrode active material for lithium secondary batteries, positive electrode for lithium secondary batteries and lithium secondary batteries
Patent Information
- Application Number
- KR1020227038325
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-07
- Filing Date
- 2021-04-27
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-04-27
Smart Images

Figure 112022115955431-PCT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a lithium metal composite oxide, a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, and a lithium secondary battery.
[0002] The present application claims priority to Japanese Patent Application No. 2020-082109 filed in Japan on May 7, 2020, and incorporates the contents thereof herein by reference. Background Technology
[0003] Lithium metal composite oxides are used as positive electrode active materials for lithium secondary batteries. Lithium secondary batteries are already being commercialized not only for small power sources such as mobile phones and laptop computers, but also for medium and large power sources such as automobiles and power storage.
[0004] The crystal structure of lithium metal composite oxides is involved in the extraction of lithium from the positive electrode during charging and the insertion of lithium during discharging. To improve the battery characteristics of lithium secondary batteries, attempts are being made to control the crystal structure of positive electrode active materials for lithium secondary batteries.
[0005] For example, Patent Document 1 describes a lithium nickel composite oxide having a crystallite diameter of 50 to 300 nm calculated from the peak of the (003) plane, with the aim of providing a positive electrode active material with good initial charge / discharge efficiency and rate characteristics of a lithium secondary battery. Prior art literature
[0006] WO 2014 / 010448A1 The problem to be solved
[0007] There is still room for improvement in lithium metal composite oxides to further enhance battery characteristics such as cycle retention rate.
[0008] The present invention, made in consideration of the above circumstances, aims to provide a lithium metal composite oxide capable of achieving a high cycle retention rate when used as a positive electrode active material for a lithium secondary battery, a positive electrode active material for a lithium secondary battery using the same, a positive electrode for a lithium secondary battery, and a lithium secondary battery. means of solving the problem
[0009] The present invention has the following aspects.
[0010] [1] A lithium metal composite oxide having a layered structure, containing at least Li and Ni and element X, wherein element X is one or more elements selected from the group consisting of Co, Mn, Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In and Sn, and 50% cumulative volume particle size D 50 L / D, the ratio of the average primary particle size L to 50 A lithium metal composite oxide having a crystallite diameter A of 700 Å or less, calculated from diffraction peaks within the range of 2θ = 44.5 ± 1° in powder X-ray diffraction measurements using CuKα rays.
[0011] [2] 10% cumulative volume particle size D 10 L / D, which is the ratio of the above average primary particle size L to . 10 This is the lithium metal composite oxide described in [1], which is 0.6 - 3.
[0012] [3] Lithium metal composite oxide described in [1] or [2], having an average primary particle size L of 1 to 10 μm.
[0013] [4] The above 50% cumulative volume particle size D 50 A lithium metal composite oxide described in any one of [1] to [3] which is 2 - 25 μm.
[0014] [5] A lithium metal composite oxide described in any one of [1] to [4] having a BET specific surface area of 0.3 - 1.9 m² / g.
[0015] [6] A lithium metal composite oxide described in any one of [1] to [5], wherein B / A is the ratio of the crystallographic diameter B to the crystallographic diameter A, when B is the crystallographic diameter calculated from the diffraction peak within the range of 2θ = 18.5 ± 1° in powder X-ray diffraction measurements using CuKα rays.
[0016] [7] A lithium metal composite oxide described in [6], wherein the crystallite diameter B is 1300 Å or less.
[0017] [8] A lithium metal composite oxide described in any one of [1] to [7], represented by composition formula (I).
[0018] Li[Li x (Ni (1-y-z-w) Co y Mn z X1 w ) 1-x ]O2(I)
[0019] In Equation (I), X1 represents one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In and Sn, satisfying -0.1 ≤ x ≤ 0.2, 0 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.4, 0 ≤ w ≤ 0.1, and 0 < y + z + w.
[0020] [9] x in the above composition formula (I) is a lithium metal composite oxide described in [8] satisfying 0 < x ≤ 0.2.
[0021]
[10] The above composition formula (I) is a lithium metal composite oxide described in [8] or [9] satisfying 0 < y + z + w ≤ 0.3.
[0022]
[11] A positive electrode active material for a lithium secondary battery containing a lithium metal composite oxide as described in any one of [1] ~
[10] .
[0023]
[12] A positive electrode for a lithium secondary battery containing the positive electrode active material for a lithium secondary battery described in
[11] .
[0024]
[13] A lithium secondary battery having a positive electrode for a lithium secondary battery as described in
[12] . Effects of the invention
[0025] According to the present invention, a lithium metal composite oxide that can achieve a high cycle retention rate when used as a positive electrode active material for a lithium secondary battery, a positive electrode active material for a lithium secondary battery using the same, a positive electrode for a lithium secondary battery, and a lithium secondary battery can be provided. Brief explanation of the drawing
[0026] Figure 1 is a schematic diagram showing an example of a lithium secondary battery. Figure 2 is a schematic diagram showing an example of a lithium secondary battery. FIG. 3 is a schematic diagram showing a laminated structure provided by the all-solid-state lithium battery of the present embodiment. FIG. 4 is a schematic diagram showing the overall configuration of an all-solid-state lithium battery of the present embodiment. Specific details for implementing the invention
[0027] Hereinafter, a lithium metal composite oxide according to one embodiment of the present invention, a positive electrode active material for a lithium secondary battery using the same, a positive electrode for a lithium secondary battery, and a lithium secondary battery will be described. In the following plurality of embodiments, preferred examples or conditions may be shared.
[0028] In the present specification, lithium metal composite oxide is hereinafter referred to as “LiMO,” and a cathode active material for lithium secondary batteries is hereinafter referred to as “CAM.”
[0029] "Ni" refers to a nickel atom, not nickel metal, and likewise "Co," "Mn," "Zr," and "Li" refer to cobalt atoms, manganese atoms, zirconium atoms, and lithium atoms, respectively.
[0030] When a numerical range is described as, for example, “1 - 10 μm” or “1 ~ 10 μm,” it means a range from 1 μm to 10 μm, and means a numerical range including a lower limit of 1 μm and an upper limit of 10 μm.
[0031] In this embodiment, "primary particle" refers to a particle that does not have grain boundaries on the outside when observed at a field of view of 5,000x or more and 20,000x or less using a scanning electron microscope or the like.
[0032] In this embodiment, "secondary particle" refers to a particle in which the primary particle is aggregated. That is, the secondary particle is an aggregate of the primary particle.
[0033] In this embodiment, the "average primary particle diameter" is measured as follows. First, using a scanning electron microscope (SEM, e.g., JSM-5510 manufactured by Nihon Denshi Corporation), an electron beam with an acceleration voltage of 20 kV is irradiated to perform SEM observation of the object to be measured. At that time, a magnification factor is set so that the number of primary particles in the obtained image (in other words, SEM photograph) is 50 or more and 100 or less. As an example, the magnification factor may be 1,000 or more and 30,000 or less. For each primary particle in the SEM photograph, a rectangle circumscribed by the primary particle is assumed, and the dimension along the length direction of the said rectangle is taken as the primary particle diameter. The said dimension is measured for each primary particle in the SEM photograph, and the average value is taken as the average primary particle diameter.
[0034] The “crystallium diameter” can be calculated by performing powder X-ray diffraction measurements using CuKα as a source and with a measurement range of diffraction angle 2θ of 10° or more and 90° or less. For example, the crystallium diameter B calculated from a diffraction peak within the range 2θ = 18.5 ± 1° can be calculated by calculating the full width at half maximum of the diffraction peak within the range 2θ = 18.5 ± 1° and using the Scherrer formula L = Kλ / βcosθ (L: crystallium diameter, K: Scherrer constant, β: peak full width at half maximum). The crystallium diameter A calculated from a diffraction peak within the range 2θ = 44.5 ± 1° can be calculated by calculating the full width at half maximum of the diffraction peak within the range 2θ = 44.5 ± 1° and using the Scherrer formula.
[0035] Powder X-ray diffraction measurements can be performed using an X-ray diffraction device (e.g., Ultima IV, manufactured by Rigaku Inc.). Detailed conditions are described in the examples. By analyzing the powder X-ray diffraction pattern obtained from the powder X-ray diffraction measurement using analysis software (e.g., integrated powder X-ray analysis software JADE), the full width at half maximum of the diffraction peaks can be calculated.
[0036] "BET specific surface area" is a value measured by the BET (Brunauer, Emmet, Teller) method. Nitrogen gas is used as the adsorption gas for the measurement of BET specific surface area. For example, 1 g of the powder to be measured can be dried in a nitrogen atmosphere at 105°C for 30 minutes, and then measured using a BET specific surface area meter (e.g., Macsorb, manufactured by Mountec Inc. (registered trademark)) (unit: m² / g).
[0037] "Cumulative volume particle size" is measured by the laser diffraction scattering method. Specifically, 0.1 g of powder of the target to be measured, e.g., LiMO, is added to 50 ml of a 0.2 mass% aqueous sodium hexametaphosphate solution, and a dispersion is obtained in which the powder is dispersed. Next, the particle size distribution is measured using a laser diffraction scattering particle size distribution measuring device (e.g., MasterSider-2000 manufactured by Malvern Co.) on the obtained dispersion, and a cumulative particle size distribution curve based on volume is obtained.
[0038] In the obtained cumulative particle size distribution curve, the value of the particle diameter at 10% accumulation from the fine particle side is the 10% cumulative volumetric particle size D. 10 (㎛), the value of the particle diameter at 50% accumulation from the microparticle side is the 50% accumulated volume particle size D 50 It is (㎛).
[0039] "Cycle retention rate" refers to the ratio of the discharge capacity of a lithium secondary battery after repeated charging and discharging to the initial discharge capacity of the lithium secondary battery after conducting a cycle test in which the lithium secondary battery is charged and discharged a predetermined number of times under specific conditions.
[0040] In this specification, for a lithium secondary battery manufactured by the method described in <Manufacturing of a lithium secondary battery (coin-type half cell)> below, the value measured by performing a test of repeating charge-discharge cycles 50 times under the conditions shown below is defined as the cycle retention rate.
[0041] Test temperature: 25 ℃
[0042] Maximum charging voltage 4.35 V, charging current 0.5 CA, constant current constant voltage charging
[0043] Minimum discharge voltage 2.8 V, discharge current 1 CA, constant current discharge
[0044] The discharge capacity of the first cycle is set as the initial cycle capacity, and the value obtained by dividing the discharge capacity of the 50th cycle by the initial cycle capacity is calculated and this value is set as the cycle retention rate.
[0045] <LiMO>
[0046] The LiMO of the present embodiment is a LiMO having a layered structure, containing at least Li, Ni, and element X, wherein element X is one or more elements selected from the group consisting of Co, Mn, Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn, and has a 50% cumulative volume particle size D 50 L / D, the ratio of the average primary particle size L to 50This is 0.3 - 1.5, and in powder X-ray diffraction measurements using CuKα rays, the crystallite diameter A calculated from the diffraction peak within the range of 2θ = 44.5 ± 1° is 700 Å or less.
[0047] In one aspect of the present invention, LiMO consists only of primary particles.
[0048] In one aspect of the present invention, LiMO is composed of a secondary particle which is an aggregate of a primary particle and a primary particle which exists independently of the secondary particle.
[0049] In one aspect of the present invention, LiMO is a powder.
[0050] When LiMO consists of secondary particles, which are aggregates of primary particles, and primary particles that exist independently of said secondary particles, the ratio of the number of primary particles to the total number of secondary particles and primary particles contained in LiMO is preferably 20% or more, more preferably 30% or more, and particularly preferably 50% or more. The upper limit is not particularly limited, but is less than 100% and preferably 90% or less.
[0051] When calculating the number of primary particles, primary particles constituting secondary particles are not counted, and only the number of primary particles existing independently of secondary particles is counted.
[0052] In this embodiment, the ratio of the number of primary particles to the total sum of the number of secondary particles and primary particles contained in LiMO is determined by the following method. First, LiMO is placed on a conductive sheet attached to a sample stage, and the primary particles and the secondary particles, which are aggregates of the primary particles, are dispersed so that they exist independently without coming into contact with each other.
[0053] After that, SEM observation is performed by irradiating an electron beam with an acceleration voltage of 20 kV using an SEM (e.g., JSM-5510 manufactured by Nihon Denshi Corporation). Next, all particles in the SEM image are taken as the sum of the number of secondary particles and the number of primary particles.
[0054] Next, the number of primary particles that exist independently of secondary particles, included among all particles, is calculated. By dividing the obtained number of primary particles by the total sum of the number of secondary particles and primary particles, the ratio of the number of primary particles to the total sum of the number of secondary particles and primary particles is calculated. In addition, the magnification of the SEM image is adjusted so that there are 200 or more and 400 or fewer LiMO particles in the SEM image. As an example, the magnification may be 1,000 or more and 30,000 or fewer.
[0055] In cases where the proportion of secondary particles in LiMO is high, for example, when the ratio of the number of primary particles contained in LiMO is 50% or less, the L / D of LiMO 50 is less than 1. In short, the ratio of the number of secondary particles is large, and D 50 Silver is affected by the particle size of the secondary particles. The larger the particle size of the secondary particles, the higher the L / D 50 becomes a small value. In this embodiment, L / D 50 It is 0.3 or higher. L / D 50 If this is 0.3 or higher, the particle size of the secondary particles is not excessively large. Therefore, even if the primary particles of LiMO expand or contract along with the lithium ion absorption and extraction reactions when the lithium secondary battery is repeatedly charged and discharged, it is difficult for cracks to occur at the grain boundaries between the primary particles of LiMO.
[0056] In cases where the proportion of primary particles in LiMO is high, for example, when the ratio of the number of primary particles contained in LiMO is 80% or more, the L / D of LiMO50 It is 1 or more.
[0057] As described above, the primary particle size of LiMO is the dimension in the length direction of a rectangle assumed to be circumscribed by the primary particle observed in the SEM image. It is also conceivable that there exist particles with a large ratio of the length direction dimension to the width direction (hereinafter also referred to as the aspect ratio). Primary particles with a large aspect ratio are evaluated to have a larger primary particle size compared to primary particles with a small aspect ratio and the same area in the SEM image. For example, the primary particle size of primary particle P with an aspect ratio of 2 is assumed to be 2, and the area in the SEM image is 2. In contrast, the primary particle size (in other words, the diameter of the circle) of primary particle Q, which has an area in the SEM image of 2 and a circular shape, is approximately 1.60.
[0058] Here, D obtained by cumulative volumetric particle size measurement 50 It is calculated by assuming that the particle under measurement is a perfect sphere. In short, the larger the aspect ratio of a primary particle, the more its D 50 ...is calculated as a value smaller than the primary particle size. To explain using the previous example, D is obtained by measuring the cumulative volumetric particle size of the primary particle P. 50 Assuming that is a value close to 1.60, the primary particle diameter of the primary particle Q, L / D of the primary particle P 50 It becomes 1.25.
[0059] In short, LiMO containing a large amount of primary particles with a high proportion and large aspect ratios, L / D 50 The value becomes greater than this. LiMO containing a large amount of primary particles, which have a high proportion of primary particles and an aspect ratio close to 1, L / D 50 This becomes a value close to 1. L / D in this embodiment50 It is 1.5 or less. L / D 50 If this is 1.5 or less, the aspect ratio of the primary particles is not excessively large, so when LiMO is used in CAM, the chargeability of the CAM is improved, and the density of the resulting positive electrode for a lithium secondary battery can be improved. As a result, the volumetric capacity of the lithium secondary battery can be improved.
[0060] In the case where the ratio of the number of primary particles in LiMO is greater than 50% and less than 80%, L / D depends on the aspect ratio of the primary particles or the particle size of the secondary particles. 50 It can take a value of = 1 ± 0.5.
[0061] Taking the above into consideration, the L / D of the LiMO of the present embodiment 50 The value is 0.3 - 1.5, preferably 0.30 - 1.2, more preferably 0.30 - 1.0, and even more preferably 0.4 - 1.0. L / D 50 If this is 0.3 - 1.5, even if the primary LiMO particles expand or contract accompanying the lithium ion adsorption and desorption reactions when the lithium secondary battery using LiMO as a CAM undergoes repeated charging and discharging, it is difficult for cracks to occur at the grain boundaries between the primary LiMO particles. Also, L / D 50 If this is 1.5 or less, the aspect ratio of the primary particles is not excessively large, and since the primary particles of LiMO expand and contract uniformly during the lithium ion absorption and extraction reactions, it is difficult for a void to form between LiMO and the conductive material when performing cycle charging and discharging, and a good contact state can be maintained. As a result, the cycle retention rate of the lithium secondary battery can be increased.
[0062] The average primary particle size L of LiMO is preferably 1 to 10 μm, more preferably 1.5 to 8 μm, even more preferably 1.7 to 6 μm, and particularly preferably 2 to 4.5 μm. When the average primary particle size L of LiMO is 1 to 10 μm, the proportion of primary particles contained in LiMO is high. For this reason, even when the primary particles of LiMO expand or contract in conjunction with the lithium ion adsorption and desorption reactions when the lithium secondary battery using LiMO as a CAM is repeatedly charged and discharged, it is difficult for cracks to occur at the grain boundaries between the primary particles of LiMO. As a result, the cycle retention rate of the lithium secondary battery can be increased.
[0063] 50% cumulative volume particle size D of LiMO 50 It is preferably 2–25 µm, more preferably 2.5–23 µm, and even more preferably 3–20 µm. 50% cumulative volume particle size D of LiMO 50 If this is 2 to 25 μm, even if the proportion of primary particles contained in LiMO is high, it is difficult for the primary particles to aggregate and form secondary particles. For this reason, even if the primary particles of LiMO expand or contract along with the lithium ion absorption and extraction reactions when the lithium secondary battery is repeatedly charged and discharged, it is difficult for cracks to occur at the grain boundaries between the primary particles. As a result, the cycle retention rate of the lithium secondary battery can be improved.
[0064] 10% cumulative volume particle size D of LiMO 10 L / D, the ratio of the average primary particle size L of LiMO to . 10 The L / D of LiMO is preferably 0.6 to 3, more preferably 0.6 to 2.5, even more preferably 0.7 to 2.5, and particularly preferably 0.9 to 2. 10If this is 0.63, the ratio of primary particles in LiMO becomes dominant. Therefore, when using a CAM with such LiMO, the chargeability of the CAM is improved, the density of the resulting positive electrode for a lithium secondary battery is enhanced, and a good contact state between LiMO and the conductive material can be realized. As a result, the cycle retention rate of the lithium secondary battery can be improved.
[0065] In powder X-ray diffraction measurements of LiMO using CuKα rays, the crystallite diameter A calculated from the diffraction peak within the range of 2θ = 44.5 ± 1° is 700 Å or less. It is preferable that the crystallite diameter A be 680 Å or less, more preferable that it be 670 Å or less, and even more preferable that it be 650 Å or less. If the crystallite diameter A is 700 Å or less, the movement path of lithium ions moving inside the crystallite becomes shorter, so the resistance of lithium ions moving inside the crystallite can be lowered. As a result, the cycle retention rate of the lithium secondary battery can be increased.
[0066] The crystallite diameter A is preferably 450 Å or more, more preferably 480 Å or more, and even more preferably 510 Å or more. When the crystallite diameter A is 450 Å or more, the interface between crystallites within the primary particles is reduced, so the frequency of lithium ion movement between crystallites is reduced, and the movement of lithium ions on the crystallite surface is facilitated. As a result, the cycle retention rate of the lithium secondary battery can be increased.
[0067] The upper and lower limits of the crystallite diameter A can be combined arbitrarily. For example, the crystallite diameter A is preferably 450 to 680 Å, more preferably 480 to 670 Å, and even more preferably 510 to 650 Å.
[0068] In powder X-ray diffraction measurements of LiMO using CuKα rays, the crystallite diameter B calculated from the diffraction peak within the range of 2θ = 18.5 ± 1° is the size in the (003) plane of the crystallite.
[0069] The crystallite diameter B is preferably 1300 Å or less, more preferably 1200 Å or less, and even more preferably 1150 Å or less. If the crystallite diameter B is 1300 Å or less, the movement path of lithium ions moving inside the crystallite is shortened, so the resistance of lithium ions moving inside the crystallite can be lowered. As a result, the cycle retention rate of the lithium secondary battery can be increased.
[0070] The crystallite diameter B is preferably 700 Å or more, more preferably 750 Å or more, and even more preferably 800 Å or more. When the crystallite diameter B is 700 Å or more, the interface between crystallites within the particle is reduced, so the frequency of lithium ion movement between crystallites is reduced, and the movement of lithium ions on the crystallite surface is facilitated. As a result, the cycle retention rate of the lithium secondary battery can be increased.
[0071] The upper and lower limits of the crystallite diameter B can be combined arbitrarily. For example, the crystallite diameter B is preferably 700 to 1300 Å, more preferably 750 to 1200 Å, and even more preferably 800 to 1150 Å.
[0072] The ratio of crystallite diameter B to crystallite diameter A, B / A, is preferably 1.3 to 1.78, more preferably 1.33 to 1.78, even more preferably 1.33 to 1.75, and particularly preferably 1.35 to 1.7. If the ratio of crystallite diameter B to crystallite diameter A, B / A, is 1.3 or higher, the ratio of crystal growth in the (003) plane direction is large, and cracks between crystallites are unlikely to occur. As a result, the cycle retention rate of the lithium secondary battery can be increased. If the ratio of crystallite diameter B to crystallite diameter A, B / A, is 1.78 or lower, the crystallite isotropy is high, and crystal planes that perform lithium ion deintercalation during charging and discharging exist uniformly throughout the LiMO, so the initial Coulomb efficiency of the lithium secondary battery can be increased.
[0073] The BET specific surface area of LiMO is preferably 0.3 to 1.9 m² / g, more preferably 0.4 to 1.5 m² / g, and even more preferably 0.5 to 1.0 m² / g. When the BET specific surface area of LiMO is 0.3 to 1.9 m² / g, the reaction with the electrolyte on the surface of LiMO is suppressed. As a result, the cycle retention rate of the lithium secondary battery can be increased.
[0074] LiMO is a metal oxide containing at least Li, Ni, and element X, and is represented, for example, by compositional formula (I).
[0075] Li[Li x (Ni (1-y-z-w) Co y Mn z X1 w ) 1-x ]O2(I)
[0076] In Equation (I), X1 represents one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In and Sn, satisfying -0.1 ≤ x ≤ 0.2, 0 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.4, 0 ≤ w ≤ 0.1, and 0 < y + z + w.
[0077] From the perspective of obtaining a lithium secondary battery with a high cycle retention rate, x in the above formula (I) is -0.1 or higher, more preferably -0.05 or higher, and even more preferably greater than 0. Also, from the perspective of obtaining a lithium secondary battery with a higher initial Coulomb efficiency, x in the above formula (I) is 0.2 or lower, more preferably 0.08 or lower, and more preferably 0.06 or lower.
[0078] The upper and lower limits of x can be combined arbitrarily. For example, combinations include x being -0.1 to 0.2, greater than 0 and less than or equal to 0.2, -0.05 to 0.08, greater than 0 and less than or equal to 0.06, etc.
[0079] From the perspective of obtaining a lithium secondary battery with low internal resistance, y in the above formula (I) is 0 or greater, preferably greater than 0, more preferably 0.005 or greater, and even more preferably 0.05 or greater. In the above formula (I), y is 0.4 or less, preferably 0.35 or less, more preferably 0.33 or less, and even more preferably 0.30 or less.
[0080] The upper and lower limits of y can be combined arbitrarily. y is 0 to 0.4, is more preferably greater than 0 and less than or equal to 0.35, is even more preferably 0.005 to 0.35, and is particularly preferably 0.05 to 0.30.
[0081] From the perspective of obtaining a lithium secondary battery with a high cycle retention rate, z in the above formula (I) is 0 or greater, preferably 0.01 or greater, more preferably 0.02 or greater, and even more preferably 0.1 or greater. In addition, z in the above formula (I) is 0.4 or less, preferably 0.39 or less, more preferably 0.38 or less, and even more preferably 0.35 or less.
[0082] The upper and lower limits of z can be combined arbitrarily. z is 0 to 0.4, preferably 0.01 to 0.39, more preferably 0.02 to 0.38, and even more preferably 0.1 to 0.35.
[0083] From the perspective of obtaining a lithium secondary battery with low internal resistance, w in the above composition formula (I) is 0 or greater, preferably exceeding 0, more preferably 0.0005 or greater, and even more preferably 0.001 or greater. Also, from the perspective of obtaining a lithium secondary battery with a large discharge capacity at a high current rate, w in the above composition formula (I) is 0.1 or less, preferably 0.09 or less, more preferably 0.08 or less, and even more preferably 0.07 or less.
[0084] The upper and lower limits of w can be combined arbitrarily. w is 0 to 0.01, preferably greater than 0 and less than or equal to 0.09, more preferably 0.0005 to 0.08, and even more preferably 0.001 to 0.07.
[0085] From the perspective of obtaining a lithium secondary battery with a high cycle retention rate, it is preferable that y + z + w be greater than 0 and greater than 0.01, and more preferable that it be greater than 0.02. From the perspective of obtaining a lithium secondary battery with high thermal stability, it is preferable that y + z + w be less than 0.9, more preferable that it be less than 0.75, and even more preferable that it be less than 0.7.
[0086] The upper and lower limits of y + z + w can be combined arbitrarily. It is preferable that y + z + w be greater than 0 and less than or equal to 0.9, more preferable that it be 0.01 to 0.5, and even more preferable that it be 0.05 to 0.3.
[0087] From the perspective of obtaining a lithium secondary battery with a high cycle retention rate, it is preferable that X1 is one or more metals selected from the group consisting of Ti, Mg, Al, W, B, Zr, and Nb, and more preferable that X1 is one or more metals selected from the group consisting of Al, W, B, Zr, and Nb.
[0088] In addition, the composition analysis of LiMO can be performed, for example, by dissolving LiMO in hydrochloric acid and then using an inductively coupled plasma emission analyzer (SPI Nanotechnology Co., Ltd., SPS3000).
[0089] In the present embodiment, the crystal structure of LiMO is a layered structure, and it is more preferable that it be a hexagonal crystal structure or a monoclinic crystal structure.
[0090] The hexagonal crystal structure is, P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, It belongs to any one space group selected from the group consisting of P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.
[0091] Also, the monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.
[0092] Among these, in order to obtain a lithium secondary battery with a large discharge capacity, it is particularly desirable that the crystal structure be a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to C2 / m.
[0093] In the present invention, the L / D of LiMO 50 This is 0.3 - 1.5, and in addition, in powder X-ray diffraction measurements using CuKα rays of LiMO, the crystallite diameter A calculated from the diffraction peak within the range of 2θ = 44.5 ± 1° is 700 Å or less, thereby improving the cycle retention rate of a lithium secondary battery using LiMO as a CAM.
[0094] <Method for manufacturing LiMO>
[0095] The method for manufacturing LiMO according to the present embodiment is preferably a method that includes the following (1), (2) and (3) in this order.
[0096] (1) Preparation of metal composite oxides
[0097] (2) Mixture of metal complex oxide and lithium compound
[0098] (3) Calcination of a mixture of metal complex oxides and lithium compounds
[0099] Hereinafter, (1) to (3) will be explained using a method for manufacturing LiMO containing Li, Ni, Co and Mn as an example.
[0100] (1) Preparation of metal composite oxides
[0101] As a precursor for a metal complex oxide, a metal complex hydroxide is first prepared containing metal atoms other than Li, namely Ni, Co, and Mn. The metal complex hydroxide can be prepared by a batch co-precipitation method or a continuous co-precipitation method that is generally known.
[0102] Specifically, by the continuous co-precipitation method described in JP-A-2002-201028, a nickel salt solution, a cobalt salt solution, a manganese salt solution, and a complexing agent are reacted to produce Ni (1-y-z) Co y Mn z A metal complex hydroxide represented by (OH)2 (in the example of this manufacturing method, since it is assumed to include Ni, Co, and Mn, in the formula, 0 < y ≤ 0.4 and 0 < z ≤ 0.4) is prepared.
[0103] The nickel salt that is the solute of the above nickel salt solution is not particularly limited, but, for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate may be used.
[0104] As the cobalt salt that is the solute of the above cobalt salt solution, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate may be used.
[0105] As the manganese salt that is the solute of the above manganese salt solution, at least one of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate may be used.
[0106] The above metal salt is the above Ni (1-y-z) Co y Mn z It is used in a ratio corresponding to the compositional ratio of (OH)2. That is, the amount of each metal salt is specified such that the molar ratio of Ni, Co, and Mn in the mixed solution containing the metal salt corresponds to (1-yz) : y : z of the compositional formula (I) of LiMO. In addition, water is used as a solvent.
[0107] Examples of complexing agents include those capable of forming complexes with nickel ions, cobalt ions, and manganese ions in an aqueous solution, such as ammonium ion donors (ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, or ammonium fluoride, etc.), hydrazine, ethylenediamine tetraacetic acid, nitrile triacetic acid, uracil diacetic acid, and glycine.
[0108] In the process of manufacturing a metal complex hydroxide, a complexing agent may or may not be used. When a complexing agent is used, the amount of complexing agent included in a mixture containing a nickel salt solution, an optional metal salt solution, and the complexing agent is, for example, a molar ratio to the sum of the moles of the metal salts (nickel salt and optional metal salt) that is greater than 0 and 2.0 or less. In the present embodiment, the amount of complexing agent included in a mixture containing a nickel salt solution, a cobalt salt solution, a manganese salt solution, and the complexing agent is, for example, a molar ratio to the sum of the moles of the metal salts (nickel salt, cobalt salt and manganese salt) that is greater than 0 and 2.0 or less.
[0109] In the co-precipitation method, to adjust the pH value of a mixture containing a nickel salt solution, an optional metal salt solution, and a complexing agent, an alkali metal hydroxide is added to the mixture before the pH of the mixture changes from alkaline to neutral. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.
[0110] In addition, the pH value in this specification is defined as the value measured when the temperature of the mixture is 40°C. The pH of the mixture is measured when the temperature of the mixture sampled from the reaction vessel reaches 40°C. If the sampled mixture is below 40°C, the mixture is heated to 40°C and the pH is measured. If the sampled mixture exceeds 40°C, the mixture is cooled to 40°C and the pH is measured.
[0111] In addition to the above nickel salt solution, cobalt salt solution, and manganese salt solution, if a complexing agent is continuously supplied to the reaction vessel, Ni, Co, and Mn react, and Ni (1-y-z) Co y Mn z (OH)2 is generated.
[0112] During the reaction, the temperature of the reaction vessel is controlled to a range of, for example, 20 to 80 ℃, preferably 30 to 70 ℃ or less.
[0113] In addition, during the reaction, the pH value in the reaction vessel is controlled to a range of, for example, 9 to 13, preferably 10.5 to 12.4. If the pH in the reaction vessel is increased, the tap density of the metal complex hydroxide obtained tends to increase.
[0114] The material in the reaction vessel is mixed by stirring. The stirring speed is preferably 100 to 5000 rpm, and more preferably 500 to 2000 rpm. If the stirring speed is slowed down, the tap density of the resulting metal composite hydroxide tends to increase.
[0115] The reaction precipitate formed in the reaction vessel is neutralized while stirring. The time for neutralizing the reaction precipitate is preferably 1 to 20 hours, and more preferably 5 to 15 hours. If the neutralization time is extended, the tap density of the resulting metal complex hydroxide tends to increase.
[0116] Ammonium sulfate crystals may be added at the start of the reaction. When ammonium sulfate crystals are added, the amount of ammonium sulfate crystals added is preferably greater than 0 g and less than or equal to 20 g per 1 L of the volume of the reaction vessel, preferably greater than 0 g and less than or equal to 1 g, and preferably greater than 0 g and less than or equal to 0.5 g. When ammonium sulfate crystals are added, the tap density of the metal complex hydroxide obtained tends to decrease.
[0117] As described above, by appropriately adjusting the pH, stirring speed, neutralization time, and the amount of ammonium sulfate crystals added in the reaction vessel, the tap density of the metal complex hydroxide can be controlled to 0.60 g / cm³ or higher.
[0118] In the continuous co-precipitation method, a reaction vessel of the overflow type can be used to separate the formed reaction precipitate.
[0119] When producing a metal complex hydroxide by a batch co-precipitation method, examples of reaction vessels include a reaction vessel not equipped with an overflow pipe and a concentration vessel connected to an overflow pipe, and a device having a mechanism for concentrating the overflowed reaction precipitate in the concentration layer and recirculating it back to the reaction vessel.
[0120] Various gases, for example, inert gases such as nitrogen, argon, or carbon dioxide, oxidizing gases such as air or oxygen, or a mixture thereof may be supplied into the reaction vessel.
[0121] After the above reaction, the neutralized reaction precipitate is isolated. For isolation, a method of dewatering a slurry containing the reaction precipitate (co-precipitate slurry) by centrifugation or suction filtration is used.
[0122] The isolated reaction precipitate is washed, dehydrated, dried, and sieved, and a metal complex hydroxide containing Ni, Co, and Mn is obtained.
[0123] It is preferable to wash the reaction precipitate with water or an alkaline washing solution. In the present embodiment, it is preferable to wash with an alkaline washing solution, and more preferable to wash with a sodium hydroxide solution. Alternatively, washing may be performed using a washing solution containing a sulfur element. Examples of washing solutions containing a sulfur element include aqueous solutions of potassium or sodium sulfates.
[0124] The tap density of the metal composite hydroxide produced by the above is preferably 0.60 g / cm³ or higher, more preferably 0.8 g / cm³ or higher, and even more preferably 0.9 g / cm³ or higher. The tap density of the metal composite hydroxide is preferably 3.0 g / cm³ or lower, more preferably 2.0 g / cm³ or lower, and even more preferably 1.8 g / cm³ or lower. The upper and lower limits of the tap density of the metal composite hydroxide can be combined arbitrarily. For example, the tap density of the metal composite hydroxide is preferably 0.60 to 3.0 g / cm³, more preferably 0.8 to 2.0 g / cm³, and even more preferably 0.9 to 1.8 g / cm³.
[0125] The L / D of LiMO produced by using a metal complex hydroxide with a tap density of 0.60 g / cm³ or higher 50 and, the L / D of the manufactured LiMO 10 It can be controlled within the preferred range of this embodiment.
[0126] Here, the tap density corresponds to the tap volume density in JIS R 1628-1997.
[0127] Next, a metal composite hydroxide is heated to produce a metal composite oxide. Specifically, the metal composite hydroxide is heated at 400–700°C. If necessary, multiple heating processes may be performed. In this specification, the heating temperature refers to the set temperature of the heating device. In the case of multiple heating processes, it refers to the temperature when heated at the highest holding temperature among each heating process.
[0128] The heating temperature is preferably 400 to 700 ℃, and more preferably 450 to 680 ℃. If the heating temperature is below 400 ℃, there is a risk that the metal composite hydroxide will not be sufficiently oxidized. In short, if the heating temperature is 400 ℃ or higher, the metal composite hydroxide is sufficiently oxidized. If the heating temperature exceeds 700 ℃, the metal composite hydroxide is excessively oxidized, and there is a risk that the BET specific surface area of the metal composite oxide will become excessively small. In short, if the heating temperature is 700 ℃ or lower, the metal composite hydroxide is properly oxidized, and the BET specific surface area of the metal composite oxide does not become excessively small.
[0129] The time for maintaining at the above heating temperature may be 0.1 to 20 hours, and 0.5 to 10 hours is preferred. The rate of increase to the above heating temperature is, for example, 50 to 400 ℃ / hour, and the rate of decrease from the above heating temperature to room temperature is, for example, 10 to 400 ℃ / hour. In addition, as the heating atmosphere, air, oxygen, nitrogen, argon, or a mixture thereof may be used.
[0130] The L / D of LiMO produced by using a metal composite oxide obtained by adjusting the heating temperature and holding time to the above range 50 The ratio of the crystallite diameter A of LiMO and the crystallite diameter B to the crystallite diameter A of LiMO, B / A, can be controlled to a preferred range of the present embodiment.
[0131] The interior of the heating device may be in an atmosphere containing a suitable amount of oxygen. The oxidizing atmosphere may be an oxygen-containing atmosphere in which an oxidizing gas is mixed with an inert gas, or an oxidizing agent may be present under an inert gas atmosphere. By having a suitable oxidizing atmosphere within the heating device, the transition metal contained in the metal complex hydroxide is oxidized appropriately, making it easier to control the form of the metal complex oxide.
[0132] In an oxidizing atmosphere, oxygen or an oxidizing agent only requires the presence of sufficient oxygen atoms to oxidize the transition metal.
[0133] When the oxidizing atmosphere is an oxygen-containing atmosphere, the atmosphere within the reaction vessel can be controlled by methods such as passing an oxidizing gas into the reaction vessel or bubbling an oxidizing gas into the mixture.
[0134] Peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorate, hypochlorite, nitric acid, halogen, or ozone can be used as oxidizing agents.
[0135] (2) Mixture of metal complex oxide and lithium compound
[0136] This process is a process of mixing a lithium compound and a metal complex oxide to obtain a mixture.
[0137] The lithium compound used in the present embodiment may be any one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride, or a mixture of two or more thereof. Among these, either or both of lithium hydroxide and lithium carbonate are preferred.
[0138] In addition, when lithium hydroxide contains lithium carbonate, it is preferable that the content of lithium carbonate in the lithium hydroxide be 5 mass% or less.
[0139] A method for mixing the above metal composite oxide and the above lithium compound is described.
[0140] After drying the above metal composite oxide, it is mixed with a lithium compound. After drying the metal composite oxide, classification may be performed appropriately.
[0141] A lithium compound and a metal composite oxide are mixed in proportion to the composition ratio of the final product. Specifically, the lithium compound and the metal composite oxide are mixed in a ratio corresponding to the composition ratio of the composition formula (I) above. More specifically, they are mixed with a lithium salt such that the molar ratio of Li to the total number of metal atoms included in the metal composite oxide is greater than 1.0. The molar ratio of Li to the total number of metal atoms is preferably 1.05 or higher, and more preferably 1.10 or higher. The molar ratio of Li to the total number of metal atoms is preferably 1.20 or lower, and more preferably 1.15 or lower. The upper and lower limits of the molar ratio of Li to the total number of metal atoms can be combined. LiMO is obtained by calcining the mixture of the lithium compound and the metal composite oxide in a subsequent calcination process.
[0142] (3) Calcination of a mixture of metal complex oxides and lithium compounds
[0143] In this embodiment, it is preferable to calcin a mixture of a lithium compound and a metal complex oxide in the presence of an inert flux. The method of preparing LiMO using an inert flux is also called the flux method.
[0144] By calcining the mixture in the presence of an inert flux, the reaction of the mixture can be accelerated. The inert flux may remain in the LiMO after calcination, or it may be removed by washing with a cleaning solution after calcination. In the present embodiment, it is preferable to wash the LiMO after calcination using pure water or an alkaline cleaning solution. As the alkaline cleaning solution, the aforementioned alkaline cleaning solution may be used.
[0145] Typically, as the calcination temperature increases, the average primary particle size tends to increase and the BET specific surface area tends to decrease. The calcination temperature can be appropriately adjusted depending on the type of transition metal element used, and the type and amount of precipitating agent and inert flux.
[0146] The L / D of LiMO prepared by using a metal composite oxide obtained by heating a metal composite hydroxide having a tap density of 0.60 g / cm³ or higher, and by performing the flux method. 50 Both the crystallite diameter A of LiMO and LiMO can be controlled to a preferred range of this embodiment.
[0147] As a firing atmosphere, air, oxygen, nitrogen, argon, or a mixture thereof is used depending on the desired composition, and if necessary, multiple firing processes are carried out.
[0148] In this embodiment, the setting of the firing temperature should take into account the melting point of the inert flux described later, and it is preferable to perform the firing in a range of [melting point of the inert flux - 200 ℃] or higher and [melting point of the inert flux + 200 ℃] or lower.
[0149] In the present embodiment, the firing temperature is not particularly limited, but, for example, 600 to 1100 ℃ is preferred, and 650 to 1050 ℃ is more preferred.
[0150] If the calcination temperature is 600 ℃ or higher, LiMO with a robust crystal structure can be obtained. Also, if the calcination temperature is 1100 ℃ or lower, the volatilization of lithium ions on the surface of secondary particles contained in LiMO can be reduced.
[0151] In this specification, the term "sintering temperature" refers to the temperature of the atmosphere inside the kiln, and also the maximum temperature of the holding temperature in the present sintering process (hereinafter referred to as the maximum holding temperature). In the case of the present sintering process having multiple heating processes, it refers to the temperature when heated at the maximum holding temperature among each heating process.
[0152] The above upper and lower limits of the firing temperature can be combined arbitrarily.
[0153] By adjusting the holding time during calcination, the average primary particle size of the obtained LiMO can be controlled to a preferred range of the present embodiment. As the holding time increases, the average primary particle size tends to increase, and the BET specific surface area tends to decrease. The holding time during calcination can be appropriately adjusted according to the type of transition metal element used, the precipitating agent, and the type and amount of inert flux.
[0154] Specifically, the holding time during sintering is preferably 3 to 50 hours. If the holding time during sintering exceeds 50 hours, battery performance tends to substantially deteriorate due to the volatilization of lithium ions. In short, if the holding time during sintering is less than 50 hours, the degradation of battery performance due to the volatilization of lithium ions can be suppressed. If the holding time during sintering is less than 3 hours, crystal development is poor, and battery performance tends to deteriorate. In short, if the holding time during sintering is 3 hours or more, crystal development is good, and battery performance tends to improve. In addition, it is also effective to perform a preliminary sintering prior to the above sintering. The temperature of the preliminary sintering is preferably carried out in the range of 300 to 850 ℃ for 1 to 10 hours.
[0155] In the present embodiment, the heating rate of the heating process reaching the maximum holding temperature is preferably 80 ℃ / hour or more, more preferably 100 ℃ / hour or more, and particularly preferably 150 ℃ / hour or more.
[0156] The heating rate of the heating process to reach the maximum holding temperature is calculated from the time from when the heating is started until the holding temperature is reached in the firing apparatus.
[0157] It is preferable for the firing process to have multiple firing stages with different firing temperatures. For example, it is preferable to have a first firing stage and a second firing stage that is fired at a higher temperature than the first firing stage. Additionally, it may have firing stages with different firing temperatures and firing times.
[0158] The inert flux that can be used in this embodiment is not particularly limited as long as it is difficult to react with the mixture during calcination. In this embodiment, examples include one or more selected from the group consisting of fluorides of one or more elements selected from the group consisting of Na, K, Rb, Cs, Ca, Mg, Sr, and Ba (hereinafter referred to as "M"), chlorides of M, carbonates of M, sulfates of M, nitrates of M, phosphates of M, hydroxides of M, molybdates of M, and tungstates of M.
[0159] Examples of M fluorides include NaF (melting point: 993 ℃), KF (melting point: 858 ℃), RbF (melting point: 795 ℃), CsF (melting point: 682 ℃), CaF2 (melting point: 1402 ℃), MgF2 (melting point: 1263 ℃), SrF2 (melting point: 1473 ℃) and BaF2 (melting point: 1355 ℃).
[0160] Examples of chlorides of M include NaCl (melting point: 801 ℃), KCl (melting point: 770 ℃), RbCl (melting point: 718 ℃), CsCl (melting point: 645 ℃), CaCl2 (melting point: 782 ℃), MgCl2 (melting point: 714 ℃), SrCl2 (melting point: 857 ℃) and BaCl2 (melting point: 963 ℃).
[0161] Examples of carbonates of M include Na2CO3 (melting point: 854 ℃), K2CO3 (melting point: 899 ℃), Rb2CO3 (melting point: 837 ℃), Cs2CO3 (melting point: 793 ℃), CaCO3 (melting point: 825 ℃), MgCO3 (melting point: 990 ℃), SrCO3 (melting point: 1497 ℃) and BaCO3 (melting point: 1380 ℃).
[0162] Examples of M sulfates include Na2SO4 (melting point: 884 ℃), K2SO4 (melting point: 1069 ℃), Rb2SO4 (melting point: 1066 ℃), Cs2SO4 (melting point: 1005 ℃), CaSO4 (melting point: 1460 ℃), MgSO4 (melting point: 1137 ℃), SrSO4 (melting point: 1605 ℃) and BaSO4 (melting point: 1580 ℃).
[0163] Examples of nitrates of M include NaNO3 (melting point: 310 ℃), KNO3 (melting point: 337 ℃), RbNO3 (melting point: 316 ℃), CsNO3 (melting point: 417 ℃), Ca(NO3)2 (melting point: 561 ℃), Mg(NO3)2, Sr(NO3)2 (melting point: 645 ℃), and Ba(NO3)2 (melting point: 596 ℃).
[0164] Examples of M phosphates include Na3PO4, K3PO4 (melting point: 1340 ℃), Rb3PO4, Cs3PO4, Ca3(PO4)2, Mg3(PO4)2 (melting point: 1184 ℃), Sr3(PO4)2 (melting point: 1727 ℃) and Ba3(PO4)2 (melting point: 1767 ℃).
[0165] Examples of hydroxides of M include NaOH (melting point: 318 ℃), KOH (melting point: 360 ℃), RbOH (melting point: 301 ℃), CsOH (melting point: 272 ℃), Ca(OH)2 (melting point: 408 ℃), Mg(OH)2 (melting point: 350 ℃), Sr(OH)2 (melting point: 375 ℃) and Ba(OH)2 (melting point: 853 ℃).
[0166] Examples of molybdates of M include Na2MoO4 (melting point: 698 ℃), K2MoO4 (melting point: 919 ℃), Rb2MoO4 (melting point: 958 ℃), Cs2MoO4 (melting point: 956 ℃), CaMoO4 (melting point: 1520 ℃), MgMoO4 (melting point: 1060 ℃), SrMoO4 (melting point: 1040 ℃), and BaMoO4 (melting point: 1460 ℃).
[0167] Examples of tungstates of M include Na2WO4 (melting point: 687 °C), K2WO4, Rb2WO4, Cs2WO4, CaWO4, MgWO4, SrWO4, and BaWO4.
[0168] In the present embodiment, two or more of these inert fluxes may be used. When two or more are used, the melting point may be lowered. Furthermore, among these inert fluxes, for obtaining LiMO with higher crystallinity, it is preferable that the inert flux be either the carbonate or sulfate of M, or the chloride of M, or a combination thereof. Also, for M, it is preferable that either or both of sodium (Na) and potassium (K). That is, among the above, the particularly preferred inert fluxes are one or more selected from the group consisting of NaOH, KOH, NaCl, KCl, Na2CO3, K2CO3, Na2SO4, and K2SO4.
[0169] In this embodiment, K2CO3 or K2SO4 is preferred as the inert flux.
[0170] In the present embodiment, the amount of inert flux used during calcination can be appropriately adjusted. The amount of inert flux used during calcination is preferably such that the amount of inert flux (molar ratio) relative to the total amount of lithium compound and inert flux is 0.010 to 30 mol%, more preferably 0.015 to 20 mol%, and even more preferably 0.020 to 15 mol% or less.
[0171] LiMO of the present embodiment can be manufactured by the above (1) to (3). In addition to the operations of (1) to (3), the following operations may be additionally performed.
[0172] In this embodiment, it is preferable to break down the LiMO after calcination in a range of, for example, 10 minutes or more and 2 hours or less. In this embodiment, the LiMO may be broken down using, for example, a mortar, a pin mill, or a mass colloider.
[0173] The inert flux remaining in the LiMO after disintegration may be cleaned. For cleaning, pure water or an alkaline cleaning solution may be used. Examples of alkaline cleaning solutions include aqueous solutions of one or more anhydrous substances selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate, and their hydrates. In addition, ammonia may be used as the alkali.
[0174] The temperature of the cleaning solution used for cleaning is preferably 15°C or lower, more preferably 10°C or lower, and even more preferably 8°C or lower. By controlling the temperature of the cleaning solution to the above range without freezing, excessive leaching of lithium ions from the crystal structure of LiMO into the cleaning solution during cleaning can be suppressed.
[0175] In the cleaning process, a method for bringing the cleaning solution into contact with LiMO may be to add LiMO into an aqueous solution of each cleaning solution and stir. Alternatively, an aqueous solution of each cleaning solution may be used as shower water and sprayed onto the LiMO. In addition, after adding LiMO into an aqueous solution of the cleaning solution and stirring, LiMO may be separated from the aqueous solution of each cleaning solution, and then an aqueous solution of each cleaning solution may be used as shower water and sprayed onto the separated LiMO.
[0176] In the cleaning process, it is desirable to bring the cleaning solution into contact with LiMO for an appropriate time range. The "appropriate time" in the cleaning process refers to a time sufficient to disperse each particle of LiMO while removing the inert flux remaining on the surface of the LiMO. The cleaning time is preferably adjusted according to the aggregation state of the LiMO. For example, a cleaning time in the range of 5 minutes to 1 hour is particularly preferred.
[0177] In this embodiment, it is preferable to further heat-treat the LiMO after cleaning the LiMO. Although the temperature or method of heat-treating the LiMO is not particularly limited, from the viewpoint of preventing a decrease in charge capacity, it is preferable that the temperature be 300°C or higher, more preferable that it be 350°C or higher, and even more preferable that it be 400°C or higher. In addition, although there are no particular limitations, from the viewpoint of preventing the volatilization of lithium ions and obtaining LiMO having the composition of this embodiment, it is preferable that the temperature be 1000°C or lower, and more preferable that it be 950°C or lower.
[0178] The volatility of lithium ions can be controlled by the heat treatment temperature.
[0179] The upper and lower limits of the heat treatment temperature can be combined arbitrarily. For example, the heat treatment temperature is preferably 300 to 1000 ℃, more preferably 350 to 950 ℃, and even more preferably 400 to 950 ℃.
[0180] Examples of the atmosphere during heat treatment include an oxygen atmosphere, an inert atmosphere, a reduced pressure atmosphere, or a vacuum atmosphere. By performing the heat treatment after cleaning in the above atmosphere, the reaction between LiMO and moisture or carbon dioxide in the atmosphere is suppressed during the heat treatment, and LiMO with low impurity content is obtained.
[0181] <CAM>
[0182] The CAM of the present embodiment contains LiMO. In the CAM of the present embodiment, the content ratio of LiMO to the total mass (100 mass%) of the CAM is preferably 70 to 99 mass%, and more preferably 80 to 98 mass%.
[0183] In this embodiment, the content ratio of LiMO to the total mass of CAM is determined by performing SEM observation on CAM using an SEM (e.g., JSM-5510 manufactured by Nihon Denshi Corporation) by irradiating it with an electron beam having an acceleration voltage of 20 kV. The magnification of the SEM image is adjusted so that there are 200 to 400 particles of the target CAM in the SEM image. As an example, the magnification may be 1,000 to 30,000 times.
[0184] <Lithium Secondary Battery>
[0185] Next, the configuration of a preferred lithium secondary battery when using the LiMO of the present embodiment as a CAM will be described.
[0186] The CAM is preferably composed of the LiMO of the present embodiment, but may contain other components within a range that does not impede the effects of the present invention. For example, the content ratio of the LiMO of the present embodiment to the total mass (100 mass%) of the CAM for a lithium secondary battery is preferably 70 to 99 mass%, and more preferably 80 to 98 mass%.
[0187] In addition, a positive electrode for a lithium secondary battery that is preferred when using the LiMO of the present embodiment as a CAM (hereinafter referred to as the positive electrode) will be described.
[0188] In addition, a lithium secondary battery suitable for use as a positive electrode is described.
[0189] An example of a preferred lithium secondary battery when using the LiMO of the present embodiment as a CAM comprises a positive electrode and a negative electrode, a separator placed between the positive electrode and the negative electrode, and an electrolyte placed between the positive electrode and the negative electrode.
[0190] An example of a lithium secondary battery has a positive electrode and a negative electrode, a separator placed between the positive electrode and the negative electrode, and an electrolyte placed between the positive electrode and the negative electrode.
[0191] FIGS. 1 and FIGS. 2 are schematic diagrams showing an example of a lithium secondary battery. The cylindrical lithium secondary battery (10) of the present embodiment is manufactured as follows.
[0192] First, as shown in FIG. 1, a pair of separators (1) having a strip shape, a strip-shaped positive electrode (2) having a positive electrode lead (21) at one end, and a strip-shaped negative electrode (3) having a negative electrode lead (31) at one end are stacked in the order of separator (1), positive electrode (2), separator (1), and negative electrode (3) and wound to form an electrode group (4).
[0193] Next, as shown in FIG. 2, an electrode group (4) and an insulator (not shown) are placed in a battery can (5), the bottom of the can is sealed, and an electrolyte (6) is impregnated into the electrode group (4) to place the electrolyte between the positive electrode (2) and the negative electrode (3). Additionally, a lithium secondary battery (10) can be manufactured by sealing the top of the battery can (5) with a top insulator (7) and a sealing body (8).
[0194] As for the shape of the electrode group (4), for example, the cross-sectional shape when the electrode group (4) is cut perpendicular to the axis of the winding can be a circle, an ellipse, a rectangle, or a columnar shape with rounded corners.
[0195] In addition, the shape of the lithium secondary battery having such an electrode group (4) may be adopted from the shape specified in IEC 60086, a battery standard set by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, shapes such as cylindrical or prismatic shapes may be used.
[0196] In addition, the lithium secondary battery is not limited to the above-mentioned wound configuration, but may also have a stacked configuration in which a stacked structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of stacked lithium secondary batteries include so-called coin-type batteries, button-type batteries, or paper-type (or sheet-type) batteries.
[0197] Below, each component will be explained in turn.
[0198] (Straight play)
[0199] A positive electrode can be manufactured by first preparing a positive electrode mixture containing a CAM, a conductive material, and a binder, and then supporting the positive electrode mixture on a positive electrode current collector.
[0200] (Challenge)
[0201] Carbon materials can be used as the conductive material for the positive electrode. Examples of carbon materials include graphite powder, carbon black (e.g., acetylene black), and fibrous carbon materials.
[0202] The ratio of conductive material in the positive electrode composite is preferably 5 to 20 parts by mass per 100 parts by mass of CAM.
[0203] (bookbinder)
[0204] As a binder for the positive electrode, a thermoplastic resin may be used. Examples of such thermoplastic resins include polyimide resin; polyvinylidene fluoride (hereinafter referred to as PVdF); fluoropolymer resins such as polytetrafluoroethylene; polyolefin resins such as polyethylene and polypropylene; and resins described in WO 2019 / 098384A1 or US 2020 / 0274158A1.
[0205] These thermoplastic resins may be used by mixing two or more types. Fluoropolymer resin and polyolefin resin are used as binders, and by setting the ratio of fluoropolymer resin to the total positive electrode composite to 1 mass% or more and 10 mass% or less, and the ratio of polyolefin resin to 0.1 mass% or more and 2 mass% or less, a positive electrode composite with high adhesion to the positive electrode current collector and high bonding strength within the positive electrode composite can be obtained.
[0206] (The entire drama house)
[0207] As the positive electrode current collector having the positive electrode, a strip-shaped member made of a metal material such as Al, Ni, or stainless steel can be used.
[0208] A method for supporting a positive electrode mixture on a positive electrode current collector includes using an organic solvent to form a paste of the positive electrode mixture, applying the resulting paste of the positive electrode mixture to at least one side of the positive electrode current collector, drying it, and pressing it to fix it.
[0209] When forming a positive electrode mixture into a paste, an organic solvent that can be used is N-methyl-2-pyrrolidone (hereinafter referred to as NMP).
[0210] Methods for applying a positive electrode paste to a positive electrode current collector include, for example, slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying.
[0211] By the method described above, a positive electrode can be manufactured.
[0212] (Polar)
[0213] The negative electrode of a lithium secondary battery can be formed by enabling doping and undoping of lithium ions at a lower potential than that of the positive electrode, and may include an electrode formed by a negative electrode composite containing a negative electrode active material supported on a negative electrode current collector, and an electrode formed by a negative electrode active material alone.
[0214] (Negative electrode active material)
[0215] Examples of negative electrode active materials include carbon materials, chalcogen compounds (oxides or sulfides, etc.), nitrides, metals, or alloys, which are materials capable of doping or undoping lithium ions at a potential lower than that of the positive electrode.
[0216] Carbon materials that can be used as negative electrode active materials include graphite such as natural graphite or artificial graphite, coke, carbon black, carbon fiber, and sintered organic polymer compounds.
[0217] Oxides usable as negative electrode active materials include SiO2 and SiO2, etc., of the formula SiO2 x Oxides of silicon represented by (where x is a positive real number); SnO2 and SnO2, etc. x Tin oxide represented by (where x is a positive real number); and Li4Ti5O 12 Examples include metal complex oxides containing lithium and titanium or vanadium, such as LiVO2.
[0218] In addition, metals that can be used as negative electrode active materials include lithium metal, silicon metal, and tin metal. Materials described in WO 2019 / 098384A1 or US 2020 / 0274158A1 may be used as materials that can be used as negative electrode active materials.
[0219] These metals or alloys are processed into thin sheets, for example, and are mainly used alone as electrodes.
[0220] Among the above negative electrode active materials, a carbon material having graphite as the main component, such as natural graphite or synthetic graphite, is preferably used for reasons such as the negative electrode potential remaining almost unchanged from the uncharged state to the fully charged state during charging (good potential flatness), a low average discharge potential, and a high capacity retention rate when subjected to repeated charge-discharge (good cycle characteristics). The shape of the carbon material may be any of the following: flake-like, such as natural graphite; spherical, such as mesocarbon micro beads; fibrous, such as graphitized carbon fibers; or aggregates of fine powder.
[0221] The above negative electrode composite may contain a binder as needed. Examples of binders include thermoplastic resins, specifically PVdF, thermoplastic polyimide, carboxymethylcellulose (hereinafter referred to as CMC), styrene-butadiene rubber (hereinafter referred to as SBR), polyethylene, and polypropylene.
[0222] (The entire Bu-geuk house)
[0223] Examples of negative current collectors for the negative electrode include strip-shaped members made of metal materials such as Cu, Ni, or stainless steel.
[0224] Methods for supporting a negative electrode composite on such a negative electrode current collector include, as with the positive electrode, a method by pressure molding, a method of forming a paste using a solvent and applying it onto the negative electrode current collector, or a method of pressing it after drying.
[0225] (Separator)
[0226] As a separator for a lithium secondary battery, materials having the form of a porous membrane, nonwoven fabric, or woven fabric, made of materials such as polyolefin resins like polyethylene and polypropylene, fluoropolymers, or nitrogen-containing aromatic polymers, may be used. In addition, a separator may be formed by using two or more of these materials, or by stacking these materials. Also, a separator described in JP-A-2000-030686 or US 20090111025A1 may be used.
[0227] (Electrolyte)
[0228] The electrolyte of a lithium secondary battery contains an electrolyte and an organic solvent.
[0229] Examples of electrolytes included in the electrolyte include lithium salts such as LiClO4 and LiPF6, and a mixture of two or more of these may be used. In addition, electrolytes described in WO 2019 / 098384A1 or US 2020 / 0274158A1 may be used.
[0230] In addition, as an organic solvent included in the above electrolyte, carbonates such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethylmethyl carbonate may be used. Also, as an organic solvent included in the electrolyte, an organic solvent described in WO 2019 / 098384A1 or US2020 / 0274158A1 may be used.
[0231] As for organic solvents, it is preferable to use a mixture of two or more of these, and a mixed solvent of cyclic carbonates and acyclic carbonates and a mixed solvent of cyclic carbonates and ethers are even more preferable.
[0232] In addition, as the safety of the resulting lithium secondary battery is enhanced, it is preferable to use an electrolyte containing a lithium salt containing fluorine, such as LiPF6, and an organic solvent having a fluorine substituent.
[0233] All-solid-state lithium secondary battery
[0234] Next, while describing the composition of an all-solid-state lithium secondary battery, a positive electrode using LiMO related to one embodiment of the present invention as a CAM for an all-solid-state lithium secondary battery, and an all-solid-state lithium secondary battery having said positive electrode will be described.
[0235] FIGS. 3 and 4 are schematic diagrams illustrating an example of an all-solid-state lithium secondary battery according to the present embodiment. The all-solid-state lithium secondary battery (1000) shown in FIGS. 3 and 4 has a laminate (100) having a positive electrode (110), a negative electrode (120), and a solid electrolyte layer (130), and an outer body (200) that accommodates the laminate (100). In addition, the all-solid-state lithium secondary battery (1000) may have a bipolar structure in which a positive electrode active material and a negative electrode active material are arranged on both sides of a current collector. As a specific example of a bipolar structure, the structure described in JP-A-2004-95400 may be cited. The materials constituting each component will be described later.
[0236] The laminate (100) may have an external terminal (113) connected to a positive electrode current collector (112) and an external terminal (123) connected to a negative electrode current collector (122). Additionally, the all-solid-state lithium secondary battery (1000) may have a separator between the positive electrode (110) and the negative electrode (120).
[0237] The all-solid-state lithium secondary battery (1000) additionally has an insulator (not shown) that insulates the laminate (100) and the outer body (200), and a sealing body (not shown) that seals the opening (200a) of the outer body (200).
[0238] The outer body (200) may be a container formed from a metal material with high corrosion resistance, such as aluminum, stainless steel, or nickel-plated steel. Additionally, as the outer body (200), a container formed by processing a laminate film, which has been treated with corrosion resistance on at least one surface, into a pocket shape may be used.
[0239] The shapes of the all-solid-state lithium secondary battery (1000) include, for example, coin type, button type, paper type (or sheet type), cylindrical type, prismatic type, or laminate type (pouch type).
[0240] The all-solid-state lithium secondary battery (1000) is illustrated as having one laminate (100) as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery (1000) may be configured such that the laminate (100) is a unit cell and a plurality of unit cells (laminated (100)) are sealed inside an outer body (200).
[0241] Below, each component will be explained in turn.
[0242] (Straight play)
[0243] The positive electrode (110) of this embodiment has a positive electrode active material layer (111) and a positive electrode current collector (112).
[0244] The positive electrode active material layer (111) comprises LiMO and a solid electrolyte, which is one embodiment of the present invention described above. Additionally, the positive electrode active material layer (111) may also include a conductive material and a binder.
[0245] (Solid electrolyte)
[0246] As the solid electrolyte included in the positive electrode active material layer (111) of the present embodiment, a solid electrolyte used in known all-solid-state batteries having lithium ion conductivity may be employed. Examples of such solid electrolytes include inorganic electrolytes and organic electrolytes. Examples of inorganic electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes. Examples of organic electrolytes include polymer-based solid electrolytes. Examples of each electrolyte include compounds described in WO 2020 / 208872A1, US 2016 / 0233510A1, US 2012 / 0251871A1, and US 2018 / 0159169A1, and examples include the following compounds.
[0247] (Oxide-based solid electrolyte)
[0248] Examples of oxide-based solid electrolytes include perovskite-type oxides, NASICON-type oxides, LISICON-type oxides, and garnet-type oxides. Specific examples of each oxide include compounds described in WO 2020 / 208872A1, US 2016 / 0233510A1, and US 2020 / 0259213A1, and examples include the following compounds.
[0249] As for garnet-type oxides, Li7La3Zr2O 12 Examples include Li-La-Zr system oxides such as (also known as LLZ).
[0250] Oxide-based solid electrolytes may be crystalline or amorphous materials.
[0251] (Sulride-based solid electrolytes)
[0252] Sulfide-based solid electrolytes include Li2S-P2S5 compounds, Li2S-SiS2 compounds, Li2S-GeS2 compounds, Li2S-B2S3 compounds, Li2S-P2S3 compounds, LiI-Si2S-P2S5 compounds, LiI-Li2S-P2O5 compounds, LiI-Li3PO4-P2S5 compounds, and Li10 GeP2S 12 You can lift the back.
[0253] In addition, in this specification, the expression "system compound" referring to a sulfide-based solid electrolyte is used as a general term for solid electrolytes that mainly contain raw materials such as "Li2S" and "P2S5" listed prior to "system compound." For example, Li2S-P2S5 system compounds include solid electrolytes that mainly contain Li2S and P2S5 and additionally contain other raw materials. The proportion of Li2S contained in the Li2S-P2S5 system compound is, for example, 50 to 90 mass% with respect to the entire Li2S-P2S5 system compound. The proportion of P2S5 contained in the Li2S-P2S5 system compound is, for example, 10 to 50 mass% with respect to the entire Li2S-P2S5 system compound. Also, the proportion of other raw materials contained in the Li2S-P2S5 system compound is, for example, 0 to 30 mass% with respect to the entire Li2S-P2S5 system compound. In addition, Li2S-P2S5-based compounds also include solid electrolytes with different mixing ratios of Li2S and P2S5.
[0254] Examples of Li2S-P2S5-based compounds include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc.
[0255] Examples of Li2S-SiS2-based compounds include Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, and Li2S-SiS2-P2S5-LiCl.
[0256] Examples of Li2S-GeS2-based compounds include Li2S-GeS2 and Li2S-GeS2-P2S5.
[0257] Sulfide-based solid electrolytes may be crystalline or amorphous materials.
[0258] Two or more types of solid electrolytes may be used in combination to the extent that they do not impede the effects of the invention.
[0259] (Challenge material and binder)
[0260] As the conductive material having the positive electrode active material layer (111) of this embodiment, the material described in the above description (conductive material) can be used. In addition, the ratio of the conductive material in the positive electrode composite can also be applied in the same way as the ratio described in the above description (conductive material). In addition, as the binder having the positive electrode, the material described in the above description (binder) can be used.
[0261] (The entire drama house)
[0262] For the positive electrode current collector (112) of the positive electrode (110) of this embodiment, the material described in the above description (positive electrode current collector) can be used.
[0263] One method of supporting the positive electrode active material layer (111) on the positive electrode current collector (112) is to press-form the positive electrode active material layer (111) on the positive electrode current collector (112). A cold press or a hot press can be used for press-forming.
[0264] In addition, a mixture of CAM, a solid electrolyte, a conductive material, and a binder may be paste-formed into a positive electrode composite using an organic solvent, and the resulting positive electrode composite may be applied to at least one surface of a positive electrode current collector (112), dried, and fixed by pressing, thereby supporting a positive electrode active material layer (111) on the positive electrode current collector (112).
[0265] In addition, a mixture of CAM, a solid electrolyte, and a conductive material may be paste-formed using an organic solvent to form a positive electrode composite, and the resulting positive electrode composite may be applied to at least one surface of a positive electrode current collector (112), dried, and sintered to support a positive electrode active material layer (111) on the positive electrode current collector (112).
[0266] As for the organic solvent that can be used for the positive electrode composite, the same organic solvent that can be used when the positive electrode composite described in the above description (positive electrode current collector) is formed into a paste can be used.
[0267] One method for applying the positive electrode mixture to the positive electrode current collector (112) is the method described above (positive electrode current collector).
[0268] By the method described above, a positive electrode (110) can be manufactured.
[0269] (Polar)
[0270] The negative electrode (120) has a negative electrode active material layer (121) and a negative electrode current collector (122). The negative electrode active material layer (121) includes a negative electrode active material. Additionally, the negative electrode active material layer (121) may include a solid electrolyte and a conductive material. The negative electrode active material, negative electrode current collector, solid electrolyte, conductive material, and binder may be those described above.
[0271] Methods for supporting a negative electrode active material layer (121) on a negative electrode current collector (122) include, as in the case of a positive electrode (110), a method by pressure molding, a method by applying a paste-like negative electrode mixture containing a negative electrode active material onto a negative electrode current collector (122), drying, and then pressing to compress, and a method by applying a paste-like negative electrode mixture containing a negative electrode active material onto a negative electrode current collector (122), drying, and then sintering.
[0272] (Solid electrolyte layer)
[0273] The solid electrolyte layer (130) has the solid electrolyte described above.
[0274] The solid electrolyte layer (130) can be formed by depositing an inorganic solid electrolyte on the surface of the positive electrode active material layer (111) of the positive electrode (110) described above by sputtering.
[0275] Additionally, the solid electrolyte layer (130) can be formed by applying a paste-like mixture containing a solid electrolyte to the surface of the positive electrode active material layer (111) of the positive electrode (110) described above, and drying it. After drying, the solid electrolyte layer (130) may be formed by press molding and further applying pressure by cold isostatic pressing (CIP).
[0276] The laminate (100) can be manufactured by laminating a negative electrode (120) so that the negative electrode electrolyte layer (121) comes into contact with the surface of the solid electrolyte layer (130) using a known method with respect to the solid electrolyte layer (130) formed on the positive electrode (110) as described above.
[0277] In a lithium secondary battery with the above configuration, since the CAM uses the LiMO manufactured according to the present embodiment described above, the cycle retention rate of the lithium secondary battery using this CAM can be improved.
[0278] In addition, the positive electrode with the above configuration can improve the cycle retention rate of the lithium secondary battery because it has the CAM with the configuration described above.
[0279] In addition, a lithium secondary battery with the above configuration becomes a secondary battery with a high cycle retention rate because it has the positive electrode described above.
[0280] Another aspect of the present invention includes the following embodiments.
[0281]
[14] A lithium metal composite oxide having a layered structure, containing at least Li and Ni and element X, and L / D 50 A lithium metal complex oxide having a g / m² value of 0.30 - 1.0 and an A value of 480 - 670 Å.
[0282]
[15] L / D 10 This lithium metal composite oxide is 0.6 - 2.5 as described in
[14] .
[0283]
[16] Lithium metal composite oxide described in
[14] or
[15] , where L is 2 - 4.5 μm.
[0284]
[17] The above D 50 A lithium metal composite oxide described in any one of
[14] to
[16] that is 3 - 20 μm.
[0285]
[18] A lithium metal composite oxide described in any one of
[14] to
[17] with a BET specific surface area of 0.5 - 1.0 m² / g.
[0286]
[19] A lithium metal composite oxide described in any one of
[14] to
[18] with a B / A of 1.33 - 1.78.
[0287]
[20] The lithium metal composite oxide described in
[19] , in which B is 800 - 1150 Å.
[0288]
[21] A lithium metal composite oxide represented by composition formula (I), as described in any one of
[14] to
[20] .
[0289] Li[Li x (Ni (1-y-z-w) Co y Mn z X1 w ) 1-x ]O2(I)
[0290] In formula (I), X1 represents one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In and Sn, satisfying -0.1 ≤ x ≤ 0.2, 0 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.4, and 0 ≤ w ≤ 0.1.
[0291]
[22] x in the above composition formula (I) is a lithium metal composite oxide described in
[21] satisfying -0.05 to 0.08.
[0292]
[23] The above composition formula (I) is a lithium metal composite oxide described in
[21] or
[22] satisfying 0.05 ≤ y + z + w ≤ 0.3.
[0293]
[24]
[14] ~
[23] A positive electrode active material for a lithium secondary battery containing a lithium metal composite oxide as described in any one of
[24]
[14] ~
[23] .
[0294]
[25]
[24] A positive electrode for a lithium secondary battery containing the positive electrode active material for a lithium secondary battery described in
[25]
[24] .
[0295]
[26] A lithium secondary battery having a positive electrode for a lithium secondary battery as described in
[25] .
[0296] Examples
[0297] The present invention will be described in detail below with reference to examples, but the present invention is not limited by the description below.
[0298] <Composition Analysis>
[0299] The composition analysis of LiMO produced by the method described below was carried out using an inductively coupled plasma emission analyzer (S.I. Nanotechnology Co., Ltd., SPS3000) and the method described above.
[0300] <Average 1st-order particle size>
[0301] The average primary particle size of LiMO was determined using a scanning electron microscope (SEM, e.g., JSM-5510 manufactured by Nihon Denshi Corporation) in the method described above. During SEM observation, the magnification was set to 5000x so that there were 50 to 100 primary particles in the SEM image.
[0302] <Cumulative Volume Particle Size Measurement>
[0303] LiMO's D 50 and D 10 It was measured using the method described above.
[0304] <Determinant Diameter>
[0305] The crystallite diameter of LiMO was determined using the method described above, with an X-ray diffraction device (Ultima IV manufactured by Rigaku Co., Ltd.) and integrated powder X-ray analysis software JADE.
[0306] <BET Specific Surface Area Measurement>
[0307] The BET specific surface area of LiMO was measured using the method described above with a BET specific surface area meter (manufactured by Mounttec, Macsorb (registered trademark)).
[0308] <Tap Density>
[0309] The tap density of the metal complex hydroxide was measured by the method described in JIS R 1628-1997.
[0310] <Fabrication of Positive Electrode for Lithium Secondary Batteries>
[0311] A paste-like positive electrode composite was prepared by adding and mixing LiMO obtained by the manufacturing method described below, acetylene black as a conductive material, and PVdF as a binder, such that the composition was LiMO : conductive material : binder = 92 : 5 : 3 (mass ratio). When preparing the positive electrode composite, NMP was used as an organic solvent.
[0312] The obtained positive electrode composite was coated onto an Al foil with a thickness of 40 μm serving as a current collector and vacuum dried at 150°C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of this positive electrode for a lithium secondary battery was set to 1.65 cm².
[0313] <Production of Lithium Secondary Battery (Coin-type Half Cell)>
[0314] The following operations were performed inside an argon-atmosphere glove box.
[0315] The positive electrode for a lithium secondary battery prepared in <Preparation of a positive electrode for a lithium secondary battery> was placed with the aluminum foil side facing downward on the lower cover of a part for a coin-type battery R2032 (manufactured by Hosen Corporation), and a laminated film separator (a laminate with a thickness of 16 μm in which a heat-resistant porous layer is laminated on top of a polyethylene porous film) was placed on top of it. 300 μl of electrolyte was injected into it. The electrolyte used was a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a 16:10:74 (volume ratio) ratio, in which LiPF6 was dissolved to a concentration of 1.3 mol / L and vinylene carbonate was dissolved at 1.0%.
[0316] Next, using metallic lithium as the negative electrode, the negative electrode was placed on the upper side of a laminated film separator, the upper cover was placed with a gasket interposed, and the battery was caulked with a caulking machine to produce a lithium secondary battery (coin-type half cell R2032. Hereinafter referred to as "coin-type half cell").
[0317] <Cycling Test>
[0318] The cycle retention rate of the lithium secondary battery was carried out under the conditions and methods described above.
[0319] Example 1
[0320] 1. Manufacture of LiMO-1
[0321] After adding water to a reaction vessel equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the liquid temperature was maintained at 50°C.
[0322] A mixed raw material solution was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution such that the atomic ratio of Ni, Co, and Mn was 0.88:0.08:0.04.
[0323] Next, the mixed raw material solution and an aqueous ammonium sulfate solution were continuously added into the reaction vessel under stirring, using them as a complexing agent. For 500 L of the solution in the reaction vessel, an aqueous sodium hydroxide solution was added dropwise while stirring at a stirring speed of 750 rpm until the pH of the solution in the reaction vessel reached 12.4 (measured temperature: 40 ℃). After 12.5 hours, the dropwise addition of the aqueous sodium hydroxide solution was stopped, and reaction precipitate 1 was obtained.
[0324] After washing reaction precipitate 1, it was dehydrated, dried, and sieved to obtain metal complex hydroxide 1 containing Ni, Co, and Mn. The tap density of metal complex hydroxide 1 was 1.56 g / cm³.
[0325] Metal complex hydroxide 1 was heated in an atmospheric atmosphere at 650°C for 5 hours and cooled to room temperature to obtain metal complex oxide 1.
[0326] Lithium hydroxide was weighed so that the amount of Li (molar ratio) relative to the total amount of Ni, Co, and Mn contained in metal complex oxide 1 was 1.1. Potassium sulfate was weighed so that the amount of potassium sulfate (molar ratio) relative to the total amount of the inert flux, potassium sulfate, and lithium hydroxide was 10 mol%. A mixture was obtained by mixing metal complex oxide 1, lithium hydroxide, and potassium sulfate using a mortar and pestle.
[0327] Next, the obtained mixture was calcined in an oxygen atmosphere at 650°C for 5 hours, cooled to room temperature, and then ground.
[0328] Subsequently, the product was calcined by maintaining it at 850°C in an oxygen atmosphere for 5 hours, and then cooled to room temperature to obtain a calcined product. The obtained calcined product was crudely crushed using a roll mill, and then milled using a disc mill (Super Mass Colloider MKCA6-2J manufactured by Masco Industry Co., Ltd.) at a gap of 100 μm and 1200 rpm, thereby D 50It was ground to a size of 100 μm or less.
[0329] Afterwards, it was fed into a pin mill (Impact Mill AVIS-100 Mill System Co., Ltd.) operated at an additional rotational speed of 16,000 rpm to crush it, and crushed powder 1 was obtained.
[0330] The crushed powder 1 was dispersed in pure water at 5°C and then dehydrated. In addition, the powder was washed using pure water adjusted to a liquid temperature of 5°C, dehydrated, and heat-treated by calcining at 760°C for 5 hours in an oxygen atmosphere to obtain powdered LiMO-1.
[0331] 2. Evaluation of LiMO-1
[0332] Compositional analysis of LiMO-1 was performed, and when correlated with compositional formula (I), the results were x = 0.02, y = 0.08, z = 0.04, and w = 0. Table 1 shows the manufacturing conditions of LiMO-1 and the compositional ratio of LiMO-1.
[0333] Example 2
[0334] 1. Manufacture of LiMO-2
[0335] After adding water to a reaction vessel equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the liquid temperature was maintained at 70°C.
[0336] A mixed raw material solution was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution such that the atomic ratio of Ni, Co, and Mn was 0.91:0.07:0.02.
[0337] Next, this mixed raw material solution was continuously added into the reaction vessel under stirring. For 500 L of the solution in the reaction vessel, an aqueous sodium hydroxide solution was added dropwise while stirring at a stirring speed of 750 rpm until the pH of the solution in the reaction vessel became 10.6 (measured temperature: 40 ℃). After 12.5 hours, the addition of the aqueous sodium hydroxide solution was stopped, and reaction precipitate 2 was obtained.
[0338] Reaction precipitate 2 was washed, dehydrated, dried, and sieved, and a metal complex hydroxide 2 containing Ni, Co, and Mn was obtained. The tap density of the metal complex hydroxide 2 was 1.05 g / cm³.
[0339] Metal complex hydroxide 2 was heated in an oxygen atmosphere at 650°C for 5 hours and cooled to room temperature to obtain metal complex oxide 2.
[0340] Lithium hydroxide was weighed so that the amount of Li (molar ratio) relative to the total amount of Ni, Co, and Mn contained in metal complex oxide 2 (1) was 1.1. Potassium carbonate was weighed so that the amount of potassium carbonate (molar ratio) relative to the total amount of the inert flux, potassium carbonate, and lithium hydroxide was 10 mol%. A mixture was obtained by mixing metal complex oxide 2, lithium hydroxide, and potassium sulfate using a mortar and pestle.
[0341] Next, the obtained mixture was calcined by maintaining it at 790°C in an oxygen atmosphere for 10 hours, and then cooled to room temperature to obtain a calcined product. The obtained calcined product was crushed in a mortar and pestle, dispersed in pure water at 5°C, and then dehydrated. In addition, the powder was washed using pure water adjusted to a liquid temperature of 5°C, dehydrated, and heat-treated by calcining at 760°C in an oxygen atmosphere for 5 hours to obtain powdered LiMO-2.
[0342] 2. Evaluation of LiMO-2
[0343] Compositional analysis of LiMO-2 was performed and correlated with compositional formula (I), resulting in x = 0, y = 0.07, z = 0.02, and w = 0. Table 1 shows the manufacturing conditions of LiMO-2 and the compositional ratio of LiMO-2.
[0344] Example 3
[0345] 1. Manufacture of LiMO-3
[0346] After adding water to a reaction vessel equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the liquid temperature was maintained at 70°C.
[0347] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution, a manganese sulfate aqueous solution, and a zirconium sulfate aqueous solution were mixed such that the atomic ratio of Ni, Co, Mn, and Zr was 0.905 : 0.07 : 0.02 : 0.005, and a mixed raw material solution was prepared.
[0348] Next, this mixed raw material solution was continuously added into the reaction vessel under stirring. For 15 L of the solution in the reaction vessel, an aqueous sodium hydroxide solution was added dropwise while stirring at a stirring speed of 1500 rpm until the pH of the solution in the reaction vessel became 10.6 (measured temperature: 40 ℃). After 12.5 hours, the dropwise addition of the aqueous sodium hydroxide solution was stopped, and reaction precipitate 3 was obtained.
[0349] Reaction precipitate 3 was washed, dehydrated, dried, and sieved, and metal complex hydroxide 3 containing Ni, Co, Mn, and Zr was obtained. The tap density of metal complex hydroxide 3 was 0.99 g / cm³.
[0350] Metal complex hydroxide 3 was heated in an oxygen atmosphere at 650°C for 5 hours and cooled to room temperature to obtain metal complex oxide 3.
[0351] Lithium hydroxide was weighed so that the amount of Li (molar ratio) relative to the total amount of Ni, Co, Mn, and Zr contained in metal complex oxide 3 (1) was 1.1. Potassium carbonate was weighed so that the amount of potassium carbonate (molar ratio) relative to the total amount of the inert flux, potassium carbonate, and lithium hydroxide was 10 mol%. A mixture was obtained by mixing metal complex oxide 3, lithium hydroxide, and potassium sulfate using a mortar and pestle.
[0352] Subsequently, the obtained mixture was calcined by maintaining it at 820°C in an oxygen atmosphere for 10 hours, and then cooled to room temperature to obtain a calcined product. The obtained calcined product was crushed in a mortar and pestle, dispersed in pure water at 5°C, and then dehydrated. In addition, the powder was washed using pure water adjusted to a liquid temperature of 5°C, dehydrated, and heat-treated by calcining at 760°C in an oxygen atmosphere for 5 hours to obtain powdered LiMO-3.
[0353] 2. Evaluation of LiMO-3
[0354] Compositional analysis of LiMO-3 was performed and correlated with compositional formula (I), resulting in x = 0, y = 0.07, z = 0.02, and w = 0.004. Table 1 shows the manufacturing conditions of LiMO-3 and the compositional ratio of LiMO-3.
[0355] Comparative Example 1
[0356] 1. Preparation of LiMO-C1
[0357] A device having a reaction vessel equipped with a stirrer and an overflow pipe, a concentration tank connected to the overflow pipe, and a mechanism for circulating from the concentration tank to the reaction vessel was used, and after adding water to the reaction vessel, an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 60°C.
[0358] A mixed raw material solution was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution such that the atomic ratio of Ni, Co, and Mn was 0.88:0.08:0.04.
[0359] Next, 30 g of ammonium sulfate crystals were added to a reaction vessel for every 1 L of the vessel's volume, and under stirring, this mixed raw material solution and an aqueous ammonium sulfate solution were continuously added as a complexing agent. For 15 L of the solution in the reaction vessel, an aqueous sodium hydroxide solution was added dropwise while stirring at a stirring speed of 1500 rpm until the pH of the solution in the reaction vessel reached 12.5 (measured temperature: 40 ℃). After 26 hours, the dropwise addition of the aqueous sodium hydroxide solution was stopped, and reaction precipitate C1 was obtained.
[0360] The neutralized reaction precipitate C1 was washed, dehydrated, dried, and sieved, and a metal complex hydroxide C1 containing Ni, Co, and Mn was obtained. The tap density of the metal complex hydroxide C1 was 0.36 g / cm³.
[0361] Metal composite hydroxide C1 was heated under the same conditions as the metal composite hydroxide 1 of Example 1, and metal composite oxide C1 was obtained.
[0362] Lithium hydroxide was weighed so that the amount of Li (molar ratio) relative to the total amount of Ni, Co, and Mn contained in metal complex oxide C1 was 1.1. Potassium carbonate was weighed so that the amount of potassium carbonate (molar ratio) relative to the total amount of potassium carbonate and lithium hydroxide, which are inert fluxes, was 10 mol%. A mixture was obtained by mixing the metal complex oxide C1, lithium hydroxide, and potassium sulfate using a mortar and pestle.
[0363] Subsequently, the obtained mixture was calcined by maintaining it at 790°C in an oxygen atmosphere for 10 hours, and then cooled to room temperature to obtain a calcined product. The obtained calcined product was crushed in a mortar and pestle, dispersed in pure water at 5°C, and then dehydrated. In addition, the powder was washed using pure water adjusted to a liquid temperature of 5°C, dehydrated, and heat-treated by calcining at 760°C in an oxygen atmosphere for 5 hours to obtain powdered LiMO-C1.
[0364] 2. Evaluation of LiMO-C1
[0365] Compositional analysis of LiMO-C1 was performed, and when correlated with compositional formula (I), the results were x = -0.01, y = 0.08, z = 0.04, and w = 0. Table 1 shows the manufacturing conditions of LiMO-C1 and the compositional ratio of LiMO-C1.
[0366] Comparative Example 2
[0367] 1. Preparation of LiMO-C2
[0368] A device having a reaction vessel equipped with a stirrer and an overflow pipe, a concentration vessel connected to the overflow pipe, and a mechanism for circulating from the concentration vessel to the reaction vessel was used, and after adding water to the reaction vessel, an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 60°C.
[0369] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution, and a manganese sulfate aqueous solution were mixed such that the atomic ratio of Ni, Co, and Mn was 0.91:0.05:0.04, and a mixed raw material solution was prepared.
[0370] Next, 30 g of ammonium sulfate crystals were added to the reaction vessel for every 1 L of the vessel's volume, and under stirring, this mixed raw material solution and an aqueous ammonium sulfate solution were continuously added as a complexing agent. For 15 L of the solution in the reaction vessel, an aqueous sodium hydroxide solution was added dropwise while stirring at a stirring speed of 1500 rpm until the pH of the solution in the reaction vessel reached 12.5 (measured temperature: 40 ℃). After 35 hours, the dropwise addition of the aqueous sodium hydroxide solution was stopped, and reaction precipitate C2 was obtained.
[0371] The neutralized reaction precipitate C1 was washed, dehydrated, dried, and sieved to obtain a metal complex hydroxide C2 containing Ni, Co, and Mn. The tap density of the metal complex hydroxide C2 was 1.45 g / cm³.
[0372] Lithium hydroxide was weighed so that the amount of Li (molar ratio) relative to the total amount of Ni, Co, and Mn contained in metal complex hydroxide C2 was 1.2. Potassium sulfate was weighed so that the amount of potassium sulfate (molar ratio) relative to the total amount of the inert flux, potassium sulfate, and lithium hydroxide was 10 mol%. A mixture was obtained by mixing metal complex hydroxide C2, lithium hydroxide, and potassium sulfate using a mortar and pestle.
[0373] Next, the obtained mixture was calcined by maintaining it at 880°C in an oxygen atmosphere for 10 hours, and then cooled to room temperature to obtain a calcined product. The obtained calcined product was crushed in a mortar and pestle, dispersed in pure water at 5°C, and then dehydrated. In addition, the powder was washed using pure water adjusted to a liquid temperature of 5°C, dehydrated, and heat-treated by calcining at 760°C in an oxygen atmosphere for 5 hours to obtain powdered LiMO-C2.
[0374] 2. Evaluation of LiMO-C2
[0375] Compositional analysis of LiMO-C2 was performed, and when correlated with compositional formula (I), the results were x = -0.05, y = 0.05, z = 0.04, and w = 0. Table 1 shows the manufacturing conditions of LiMO-C2 and the compositional ratio of LiMO-C2.
[0376] Comparative Example 3
[0377] 1. Preparation of LiMO-C3
[0378] A device having a reaction vessel equipped with a stirrer and an overflow pipe, a concentration tank connected to the overflow pipe, and a mechanism for circulating from the concentration tank to the reaction vessel was used, and after adding water to the reaction vessel, an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 60°C.
[0379] A mixed raw material solution was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution such that the atomic ratio of Ni, Co, and Mn was 0.88:0.08:0.04.
[0380] Next, 30 g of ammonium sulfate crystals were added to the reaction vessel for every 1 L of the vessel's volume, and under stirring, this mixed raw material solution and an aqueous ammonium sulfate solution were continuously added as a complexing agent. For 15 L of the solution in the reaction vessel, an aqueous sodium hydroxide solution was added dropwise while stirring at a stirring speed of 1500 rpm until the pH of the solution in the reaction vessel reached 12.5 (measured temperature: 40 ℃). After 20 hours, the dropwise addition of the aqueous sodium hydroxide solution was stopped, and reaction precipitate C3 was obtained.
[0381] The neutralized reaction precipitate C3 was washed, dehydrated, dried, and sieved, and a metal complex hydroxide C3 containing Ni, Co, and Mn was obtained. The tap density of the metal complex hydroxide C3 was 0.56 g / cm³.
[0382] Metal composite hydroxide C3 was heated under the same conditions as the metal composite hydroxide 1 of Example 1, and metal composite oxide C3 was obtained.
[0383] Lithium hydroxide was weighed so that the amount of Li (molar ratio) relative to the total amount of Ni, Co, and Mn contained in the metal complex oxide C3 was 1.1. Potassium carbonate was weighed so that the amount of potassium carbonate (molar ratio) relative to the total amount of the inert flux, potassium carbonate, and lithium hydroxide was 5 mol%. A mixture was obtained by mixing the metal complex oxide C3, lithium hydroxide, and potassium carbonate using a mortar and pestle.
[0384] Next, the obtained mixture was calcined by maintaining it at 790°C in an oxygen atmosphere for 10 hours, and then cooled to room temperature to obtain a calcined product. The obtained calcined product was crushed in a mortar and pestle, dispersed in pure water at 5°C, and then dehydrated. In addition, the powder was washed using pure water adjusted to a liquid temperature of 5°C, dehydrated, and heat-treated by calcining at 760°C in an oxygen atmosphere for 5 hours to obtain powdered LiMO-C3.
[0385] 2. Evaluation of LiMO-C3
[0386] Compositional analysis of LiMO-C3 was performed, and when correlated with compositional formula (I), the results were x = 0.04, y = 0.08, z = 0.04, and w = 0. Table 1 shows the manufacturing conditions of LiMO-C3 and the compositional ratio of LiMO-C3.
[0387]
[0388] Average primary particle size L and 50% cumulative volume particle size D of LiMO-1 to LiMO-3 of Examples 1 to 3 and LiMO-C1 to LiMO-C3 of Comparative Examples 1 to 3 50 , 10% cumulative volume particle size D 10 , L / D 50 , L / D 10Table 2 shows the crystallite diameter A, crystallite diameter B, the ratio of crystallite diameter A to crystallite diameter B A / B, the BET specific surface area, and the cycle retention rate of the coin-type half cell using each LiMO.
[0389]
[0390] As shown in Table 2, the L / D of LiMO as in Examples 1 to 3 50 If this is 0.3 or higher and 1.5 or lower, and also the crystallite diameter A is 700 Å or lower, the cycle retention rate was 81% or higher. In the manufacturing methods of Examples 1 to 3, the tap density of the metal composite hydroxide, which is a precursor of LiMO, is 0.60 g / cm³ or higher, the metal composite hydroxide is heated to form a metal composite oxide, and the metal composite oxide is mixed with a lithium compound and calcined in the presence of an inert flux.
[0391] Meanwhile, LiMO's L / D 50 In Comparative Examples 1 and 3, where the value was less than 0.3, and Comparative Example 2, where the crystallite diameter A was greater than 700 Å, the cycle retention rate was less than 80%.
[0392] In the manufacturing methods of Comparative Examples 1 and 3, the tap density of the metal complex hydroxide, which is a precursor of LiMO, was less than 0.60 g / cm³.
[0393] In the manufacturing method of Comparative Example 2, the metal composite hydroxide was not heated to form a metal composite oxide, but rather the metal composite hydroxide was mixed with a lithium compound and calcined. As a result, the L / D of LiMO 50 Although it became 0.3 or higher, the result was that the crystallite diameter A exceeded 700 Å.
[0394] Industrial applicability
[0395] According to the present invention, a lithium metal composite oxide that can achieve a high cycle retention rate when used as a positive electrode active material for a lithium secondary battery, a positive electrode active material for a lithium secondary battery using the same, a positive electrode for a lithium secondary battery, and a lithium secondary battery can be provided. Explanation of the symbols
[0396] 1 : Separator 2 : Straight Drama 3 : Negative pole 4: Electrode group 5 : Battery can 6 : Electrolyte 7: Top Insulator 8 : Bongguche 10: Lithium secondary battery 21: Straight Drama Lead 31: Negative lead 100 : Laminate 110 : Straight Drama 111: Positive electrode active material layer 112 : Entire house of straight plays 113 : External terminal 120 : Pole 121 : Negative electrode active material layer 122 : Bu-geuk entire house 123 : External terminal 130: Solid electrolyte layer 200 : External body 200a : Opening 1000 : All-solid-state lithium secondary battery
Claims
Claim 1 A lithium metal composite oxide having a layered structure, comprising at least Li and Ni and element X, wherein element X is one or more elements selected from the group consisting of Co, Mn, Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn, and 50% cumulative volume particle size D 50 L / D, the ratio of the average primary particle size L to 50 A lithium metal composite oxide having a value of 0.3 to 1.5, wherein, in powder X-ray diffraction measurements using CuKα rays, the crystallite diameter A calculated from the diffraction peak within the range of 2θ = 44.5 ± 1° is 700 Å or less, and the crystallite diameter B calculated from the diffraction peak within the range of 2θ = 18.5 ± 1° is 1032 Å or more and 1300 Å or less. Claim 2 In claim 1, 10% cumulative volume particle size D 10 L / D, which is the ratio of the above average primary particle size L to . 10 This is a 0.6 - 3, lithium metal complex oxide. Claim 3 A lithium metal composite oxide according to claim 1 or 2, wherein the average primary particle size L is 1 to 10 μm. Claim 4 In claim 1 or 2, the 50% cumulative volume particle size D 50 This is a lithium metal composite oxide with a thickness of 2 - 25 µm. Claim 5 A lithium metal composite oxide according to claim 1 or 2, having a BET specific surface area of 0.3 - 1.9 m² / g. Claim 6 A lithium metal composite oxide according to claim 1 or 2, wherein B / A, the ratio of the crystallite diameter B to the crystallite diameter A, is 1.3 to 1.
78. Claim 7 In claim 1 or 2, a lithium metal composite oxide represented by compositional formula (I). Li [Li x (Ni (1-y-z-w) Co y Mn z X1 w ) 1-x ]O2(I) In equation (I), X1 represents one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In and Sn, and satisfies -0.1 ≤ x ≤ 0.2, 0 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.4, 0 ≤ w ≤ 0.1, and 0 < y + z + w. Claim 8 In claim 7, x in the composition formula (I) satisfies 0 < x ≤ 0.2, a lithium metal composite oxide. Claim 9 In claim 7, the above compositional formula (I) is a lithium metal composite oxide satisfying 0 < y + z + w ≤ 0.
3. Claim 10 A positive electrode active material for a lithium secondary battery containing a lithium metal composite oxide as described in claim 1 or 2. Claim 11 A positive electrode for a lithium secondary battery containing the positive electrode active material for a lithium secondary battery described in claim 10. Claim 12 A lithium secondary battery having a positive electrode for a lithium secondary battery as described in claim 11. Claim 13 delete
Citation Information
Patent Citations
Positive electrode active material for nonaqueous electrolyte secondary battery
JP2017188445A
Spinel-type lithium-manganese-containing composite oxide
JP6391857B2
Positive electrode active material for lithium secondary batteries, positive electrode for lithium secondary batteries, and lithium secondary battery
KR1020170009876A
Positive electrode active substance for lithium ion secondary battery and method for producing same
WO2019194150A1
Positive electrode active substance for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell
WO2020003642A1
